Research Progress of Radiomics Combined with Biomarkers for Predicting Microvascular Invasion in Liver Cancer - LIANG Jinghui; WANG Ming; CHEN Wanting; ZHANG Baoluhe; DU Shunda; YANG Meng (Xiehe Yixue Zazhi)
Microvascular invasion is one of the critical factors influencing the prognosis of patients with hepatocellular carcinoma. Accurate preoperative prediction for its occurrence holds pivotal significance for the formulation of clinical individualized treatment decisions. Traditional diagnosis primarily relies on the evaluation of postoperative histopathological results, which exhibits a certain degree of lag. However, the emergence of radiomics features and biomarkers offers new insights for the preoperative prediction of microvascular invasion. The preoperative prediction model based on radiomics and biomarkers is capable of precisely analyzing and efficiently predicting the occurrence risk of microvascular invasion from both macroscopic imaging features and microscopic molecular levels, thereby providing multi-dimensional and precise scientific evidence for clinical decision-making.